Provision of Education on the Signs of Pregnancy Danger to Pregnant Women in the Kapuas Primary Health Care Area, Central Kalimantan. - Zaiyidah Fathony; Siti Maria Ulfa; Rizki Amalia (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
Limited knowledge of pregnant women about danger signs of pregnancy poses a risk of problems in pregnancy. The purpose of this counseling is so that pregnant women can increase their knowledge and maintain health during pregnancy. The method used is counseling by exposing material about danger signs in pregnancy accompanied by evaluation of activities in the form of pretest and posttest. The result of this counseling is a significant increase in knowledge as indicated by the results of the posttest with a score of 90% for the participants. The conclusion from this activity is that the implementation of community service in the form of health education regarding danger signs of pregnancy significantly affects mother's knowledge.